Market challenges to improved pig productivity in Uganda - Ultimate Business Strategies, Ltd (International Livestock Research Institute, 2020)
This film talks about marketing issues in the smallholder pig value chain in Uganda. A 'market system's approach, which uses environmentally sustainable and gender-inclusive interventions, is being used by the CGIAR Research Program of Livestock to improve pig productivity and incomes from pig farming in Uganda. The film was produced by VAL Media and Ultimate Business Strategies after a 'market systems' training workshop for the CRP Livestock team in the country.